Team values: bringing athletes into the process successfully - Grant, M. A. (International Sport Coaching Journal, 2024)
The purpose of this practical advances article was to describe a successful process involving youth athletes in the development of shared core values for a club swim team and share lessons learned and applications found therein. A purposeful, convenience sample of local USA Swimming club swimmers participated in the development of the shared core values for their team. Data were collected through the administration of three sequential worksheets during the swimmers` winter holiday break from school. All responses were analyzed using a simplistic mixed methods approach. Results presented five shared core values with associated definitions, actions, and expectations derived directly from the athletes; the primary researcher/head coach added simple quotes from the athletes, when applicable, as an easy memory tool. Lessons learned from the process of this study and practical applications are discussed.